Vestibular schwannoma: evolution of diagnosis and treatment - Sina Radparvar (Egyptian Journal of Neurosurgery)
Abstract Background Vestibular Schwannomas are benign tumors of the vestibular branch of the eight cranial nerves usually seen in adults who present with sensorineural hearing loss and tinnitus. While there is no infiltration or invasion of brain tissue, the tumors are still dangerous lesions because of their position in the cerebellopontine angle and potential for compression in a crowded neighborhood filled with vital structures. Methods Ovid Medline and Google Scholar searches were performed to identify pertinent historical and modern research and review articles related to the topic. Findings The article reviews the evolution of diagnosis and treatments for Vestibular Schwannoma in the last century and highlights significant breakthroughs. It provides a historical perspective on this topic with emphasis on the chronological progression and advancements of various diagnostic methods and treatment approaches. The article portrays neurosurgical specialty with its enormous dimension and ancient history, as one of the most constantly changing and evolving specialties in medicine. Conclusions Diagnosis and treatment of Vestibular Schwannoma has had a lengthy and torturous history. Significant discoveries occurred in the last century with the most notable breakthroughs in the last fifty years. In this historical vignette, the evolutionary pathways for diagnosis and treatment of Vestibular Schwannoma are analyzed including the historical breakthroughs, contemporary management, and future directions.